2010
DOI: 10.1007/s11764-010-0121-2
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the psychosexual impact of cancer-related infertility in women: third-party reproductive assistance

Abstract: Introduction This study empirically assessed emotional and sexual functioning, reproductive concerns, and quality of life (QOL) of cancer-related infertile women in comparison to those without a cancer history and explored awareness of third-party reproduction options in cancer survivors. Methods One hundred twenty-two cancer survivors (Gynecologic and Bone Marrow/Stem Cell Transplant) with cancer-related infertility and 50 non-cancer infertile women completed a self-report survey assessing: reproductive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 32 publications
4
80
0
1
Order By: Relevance
“…Previous studies indicated that cancer-related infertility has a negative influence on the quality of life in cancer survivors. The psychosocial impact of fertility loss comprised psychosocial concerns, distress and poor sexual functioning (Canada and Schover, 2012;Carter et al, 2010;Howard-Anderson et al, 2012;Wenzel et al, 2005). Moreover, research suggested that most cancer survivors prefer to have a biological child, even if there are concerns about long-term additional barriers associated with limited responsibility and opportunity in fertility information provision.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that cancer-related infertility has a negative influence on the quality of life in cancer survivors. The psychosocial impact of fertility loss comprised psychosocial concerns, distress and poor sexual functioning (Canada and Schover, 2012;Carter et al, 2010;Howard-Anderson et al, 2012;Wenzel et al, 2005). Moreover, research suggested that most cancer survivors prefer to have a biological child, even if there are concerns about long-term additional barriers associated with limited responsibility and opportunity in fertility information provision.…”
Section: Introductionmentioning
confidence: 99%
“…We present data from the participants in one arm of a multigroup comparison study conducted from October 2006 to February 2009 that examined the experience of infertile women with various conditions (i.e., cancer vs. noncancer), which was published in detail elsewhere (26). Study eligibility criteria included no cancer history, 18 to 49 years of age at recruitment, history of infertility and on a wait list for oocyte donation, had not started or completed childbearing, English speaking, and able to provide informed consent.…”
Section: Materials and Methods Study Design And Patientsmentioning
confidence: 99%
“…Donation has the added advantage of preventing the passage of genetic material that may be associated with the patient's cancer (for example, BRCA genes) 8 . Despite pregnancy and live birth rates being comparable or better in donor cycles than in cycles using autologous oocytes (donor oocytes often come from young, healthy women) 95 , accessibility is a limitation 96 . Canada places restrictions on financial compensation to oocyte donors (only reimbursement of expenses incurred by the oocyte donor are allowed) and also prohibits oocyte sharing programs in which the donor receives financial incentives 97 .…”
Section: Oocyte and Sperm Donationmentioning
confidence: 99%
“…Particularly in the context of the physical morbidities that may linger after cancer, either as a result of the process itself or of the treatment (for example, cardiac toxicity, renal dysfunction, respiratory disease with certain chemotherapies, removal of female reproductive organs), the ability to maintain a pregnancy may not be possible or may be too high a risk even if cryopreserved gametes are available. In a study involving 122 cancer patients, the perceived acceptability of alternative familybuilding options (after pregnancy with autologous oocytes) was highest for adoption (43%, 53 of 122) and second highest for surrogacy (34%, 42 of 122) 96 .…”
Section: Gestational Carriers and Adoptionmentioning
confidence: 99%